2018
DOI: 10.3389/fneur.2018.00959
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Stereotactic Radiosurgery for Brain Metastases

Abstract: Stereotactic radiosurgery (SRS) is increasingly utilized to treat the resection cavity following resection of brain metastases and recent randomized trials have confirmed postoperative SRS as a standard of care. Postoperative SRS for resected brain metastases improves local control compared to observation, while also preserving neurocognitive function in comparison to whole brain radiation therapy (WBRT). However, even with surgery and SRS, rates of local recurrence at 1 year may be as high as 40%, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 46 publications
(66 reference statements)
0
38
0
2
Order By: Relevance
“…Some concerns with post-SRS include radiation necrosis and leptomeningeal disease (LMD) recurrence. The hypothesis behind LMD recurrence is the intra-operative seeding of viable tumor cells, which is supported by a study where post-SRS demonstrated higher rates of LMD compared to adjuvant WBRT [15] . A new approach, pre-operative SRS (pre-SRS), is being evaluated as a potential method to decrease radiation necrosis and LMD.…”
Section: Srsmentioning
confidence: 90%
See 1 more Smart Citation
“…Some concerns with post-SRS include radiation necrosis and leptomeningeal disease (LMD) recurrence. The hypothesis behind LMD recurrence is the intra-operative seeding of viable tumor cells, which is supported by a study where post-SRS demonstrated higher rates of LMD compared to adjuvant WBRT [15] . A new approach, pre-operative SRS (pre-SRS), is being evaluated as a potential method to decrease radiation necrosis and LMD.…”
Section: Srsmentioning
confidence: 90%
“…Potential benefits of pre-SRS include: (1) better local tumor control through improved delineation when contouring an intact metastasis compared to an irregularly-shaped surgical cavity; (2) reduced risk of radiation necrosis, as there is no need to treat surrounding brain tissue and the majority of the treated BM will be resected; (3) reduced risk of LMD as a result of a potential sterilizing effect via the intraoperative seeding of treated tumor cells; and (4) the potential to treat more patients, as with post-SRS some patients are lost to follow-up. A potential disadvantage includes reduced wound healing [15] . Asher et al [16] evaluated pre-SRS in 47 patients, demonstrating its safety and efficacy with local control rates of 85.6% at 12 months.…”
Section: Srsmentioning
confidence: 99%
“…With an end goal to positively enhance the adverse outcomes, the The important discoveries of the postoperative cavity SRS studies were the excessive rates of local recurrences (≤44%), radiation necrosis (≤49.4% in 24 months), LMD (≤31%, mostly in 1year of treatment), the considerable potential for higher neurotoxic events due to the necessity for planning target volume (PTV) margins, and target volume definition difficulties caused by the postoperative cavity dynamics [3,[43][44][45][46]. Therefore, taken together, these significant restrictions of the postoperative SRS soundly expanded the enthusiasm for PO-SRS as a theoretically valid alternative, likewise the many other tumor primaries, like rectal cancers.…”
Section: Rationale and Evidence For Po-srsmentioning
confidence: 99%
“…However, as recently shown by Prabhu et al only 2 (1.7%) of 120 patients couldn't undergo the planned surgery, because of intercurrent illnesses [54]. On the other hand, contrasted with the typical 6 to 48 hours interval between the PO-SRS and surgery, the frame-based SRS is frequently performed 2 to 5 weeks of surgery leading to a prolonged time frame provision for development of postoperative complications which may defer or cancel the intended postoperative SRS due to numerous causes including the early tumor progression [3].…”
Section: Relative Advantages and Disadvantages Of Po-srsmentioning
confidence: 99%
See 1 more Smart Citation